Extracellular Signal-Regulated Kinase 1/2 Involvement in the Enhancement of Contextual Fear Conditioning by Nicotine - Raybuck, Jonathan D. (2007)
Contextual fear conditioning is enhanced by nicotine, but the cellular mechanisms underlying this effect are unknown. Extracellular signal regulated kinase 1/2 (ERK 1/2) has been shown to play an integral role in the formation of contextual fear memories. As such, it is possible that ERK 1/2 is involved in the enhancement of contextual fear conditioning by nicotine. To determine whether ERK 1/2 plays a role in this enhancement, a dose of SL327 (a selective, systemic ERK 1/2 inhibitor) that is subthreshold for inhibiting contextual fear conditioning was coadministered with nicotine prior to training, testing, or both training and testing of contextual fear conditioning in C57BL/6 mice. When administered prior to training, this subthreshold dose of SL327 attenuated the enhancement of contextual fear conditioning by nicotine to levels similar to those of vehicle-treated animals. When administered prior to testing, the subthreshold dose of SL327 did not significantly alter conditioning. These results suggest that activation of ERK 1/2 by nicotine during acquisition leads to an enhancement of contextual fear conditioning.